Anaesthetic Considerations in Myasthenia Gravis: Strategies to Mitigate Cholinergic Crisis during Thymectomy - Chhaya Mahesh Suryawanshi; Jekha Mary Babu (Journal of Clinical and Diagnostic Research)
Myasthenia Gravis (MG) is an autoimmune neuromuscular disorder characterised by muscle weakness due to antibodies directed against acetylcholine receptors at the neuromuscular junction. Patients with MG presents with significant anaesthetic challenges, including prolonged neuromuscular blockade, higher risk for perioperative myasthenic or cholinergic crises and risk of postoperative respiratory failure, chances of delayed extubation, potential need for postoperative ventilator support and risks associated due to close proximity to mediastinal structures. Thymectomy is the key treatment for MG and these challenges are to be anticipated during procedures like Video-Assisted Thoracoscopic Thymectomy (VATS). We present the anaesthetic management of a 24-year-old female with MG and co-existing hypothyroidism, who underwent laparoscopic VATS. Anaesthesia was induced using a non-depolarising muscle relaxant under neuromuscular monitoring, along with thoracic epidural analgesia and left-sided Double Lumen Tube (DLT) to facilitate one lung ventilation. Despite thorough preoperative optimisation, the patient exhibited intraoperative signs suggestive of cholinergic crisis, most likely due to excessive anticholinesterase therapy. The crisis was promptly recognised and effectively managed by providing appropriate supportive care and discontinuing anticholinesterase therapy. Postoperatively, the patient was extubated successfully without the need for ventilator support. This case emphasises the critical role of comprehensive preoperative assessment, vigilant intraoperative monitoring, and the ability to accurately distinguish between myasthenic and cholinergic crises. It also illustrates the anaesthetic challenges associated in managing MG, particularly in patients with coexisting endocrine disorders such as hypothyroidism. Timely recognition and a tailored anaesthetic approach are essential for optimising outcomes in such complex cases.